Pengembangan Buku Saku Berorientasi Mind Mapping pada Mata Pelajaran IPAS Materi Mengubah Bentuk Energi Kelas IV SDN 24 Pontianak Kota - Juliana Juliana; Siti Halidjah; Rio Pranata (Departement of Mathematics Education, 2024)
This study aims to produce Mind Mapping-oriented pocket book products on the subject of Natural and Social Sciences (IPAS) material on changing the form of energy in grade IV Elementary School. This study uses the Research and Development (RnD) research and development method with the ADDIE model. The samples of this study were 2 validators and 25 students. The results of this study are in the form of Mind Mapping-oriented pocket books on the subject of ipas material changing the form of energy in class IV Elementary School. The results of the product feasibility test obtained an assessment according to 2 validators on the content/material aspect which obtained an average of 3.79 with the criteria